Diagnostic yield of clinical exome sequencing in adulthood in medical genetics clinics. Issue 2 (19th November 2022) - Mainali, Apurba; Athey, Taryn; Bahl, Shalini; Hung, Clara; Caluseriu, Oana; Chan, Alicia; Eaton, Alison; Ghai, Shailly Jain; Kannu, Peter; MacPherson, Melissa; Niederhoffer, Karen Y.; Siriwardena, Komudi; et al.
Abstract: Clinical exome sequencing (ES) is the most comprehensive genomic test to identify underlying genetic diseases in Canada. We performed this retrospective cohort study to investigate the diagnostic yield of clinical ES in adulthood. Inclusion criteria were: (1) Adult patients ≥18 years old; (2) Patients underwent clinical ES between January 1 and December 31, 2021; (3) Patients were seen in the Department of Medical Genetics. We reviewed patient charts. We applied American College of Medical Genetics and Genomics and the Association for Molecular Pathology variant classification guidelines for interpretation of variants. Non‐parametric Fisher's exact statistical test was used. Seventy‐seven patients underwent clinical ES. Fourteen different genetic diseases were confirmed in 15 patients: FBXO11, MYH7, MED13L, NSD2, ANKRD11 ( n = 2), SHANK3, RHOBTB2, CDKL5, TRIO, TCF4, SCN1, SMAD3, POGZ, and EIF2B3 diseases. The diagnostic yield of clinical ES was 19.5%. Patients with a genetic diagnosis had a significantly higher frequency of neurodevelopmental disorders than those with no genetic diagnosis ( p = 0.00339). The diagnostic yield of clinical ES was the highest in patients with seizures (35.7%), and with progressive neurodegenerative diseases (33.3%). Clinical ES is a helpful genomic test to provide genetic diagnoses to the patients who are referred to medical genetic clinics due to suspected genetic diseases in adulthood to end their diagnostic odyssey. Targeted next generation sequencing panels for specific phenotypes may decrease the cost of genomic test in adulthood.